The good, the bad, and the spooky - John, Jory; Joshaghani, Saba; Oswald, Pete (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2021)
"Halloween is the Bad Seed's favorite holiday of the year. But what's a seed to do when he can't find a show-stopping costume for the big night? Postpone trick-or-treating for everyone, of course! Can he get a costume together in time?"--
"The Bad Seed presents."
Companion to: The bad seed.
004-008.
Keywords: Seeds -- Juvenile fiction; Halloween -- Juvenile fiction; Halloween costumes -- Juvenile fiction; Conduct of life -- Juvenile fiction; Seeds -- Fiction; Halloween -- Fiction; Halloween costumes -- Fiction; Behavior -- Fiction; Humorous stories; Picture books; Humorous fiction